Design and Build a Website for Employee Performance Assessment on Harian Kompas Using the Key Performance Indicator (KPI) Method: Rancang Bangun Website Penilaian Kinerja Karyawan Pada Harian Kompas Menggunakan Metode Key Performance Indicator (KPI) - Lorensa, Mohammad Deo (Journal of Emerging Information Systems and Business Intelligence, 2023)
Employee performance appraisal is an important aspect carried out by the company. Company performance appraisal is carried out to evaluate the performance that has been carried out by employees using a systematic process so as to get performance results. With the implementation of performance appraisal, the ability of each employee can be identified and the company can plan employee career development. At Kompas Daily, employee performance appraisal still uses the conventional method, namely using Microsoft Excel. The assessment is carried out by sending an assessment form from superiors to human resources for validation, then sent to employees to carry out an assessment, then sent to superiors to give superiors grades, and ends at human resources to recap the assessment. In this way it is considered very ineffective at this time, therefore a website-based application was created as a solution to help conduct performance appraisals at Kompas Daily to make it more effective and make it easier to evaluate employee performance. The method used for this performance assessment is the Key Performance Indicator (KPI) which has been implemented in Kompas Daily. This research can aim to form a performance appraisal application with the systems and methods that have been implemented in Kompas Daily. By doing this research, it is hoped that this application can provide superiority in the aspects of effectiveness, objectivity and accuracy in the performance appraisal conducted on Kompas Daily.